Features of French policy in Togo during the presidency of General de Gaulle (1958-1969) (Journal of Oriental Studies, 2016)
this article discusses the features and analyze the policy of France in togo in the years 1958-1969, and the role of the doctrine of intervention of General de Gaulle.
Keywords: the mandate; autonomy; francafrica